Investigation on an ultra-compact Mach–Zehnder interferometer electro-optic switch using poled-polymer/silicon slot waveguide - Huang, Xiao-Liang; Zheng, Chuan-Tao; Sun, Chang-Lun; Li, Cui-Ting; Wang, Yi-Ding; Zhang, Da-Ming (Optical and quantum electronics, 2015)
By using poled-polymer/silicon slot waveguides in the active region and employing the Pockels effect of the poled-polymer, we propose a kind of Mach–Zehnder interferometer (MZI) electro-optic (EO) switch operated at 1550 nm. Dependencies of switching characteristics versus the slot waveguide parameters are investigated, including EO overlap integral, power ratio confined in the slot, and voltage-length product. Given the dimension of the silicon strip of 190 × 300 nm, as the slot width varies within 50–100 nm, the switching voltage can be as low as 1.0 V with only 0.17–0.35 mm active region length, and the whole device length is only about 770–950 μm. For the switch with 50 nm slot width, the insertion loss is about 4.42 dB under both operation states, and the crosstalk under cross-state and that under bar-state are about −48.2 and −65.3 dB, respectively. An impressive advantage of this switching structure lies that the voltage-length product (0.17–0.35 V mm) is at least 19–40 times smaller than that of the traditional polymer MZI EO switch (6.69 V mm). Compared with our previously reported two kinds of MZI or microring resonator assisted MZI EO switches, this switch does exhibit some superior characteristics, including low switching voltage, compact device size and small wavelength dependency, due to the use of slot waveguides in the MZI EO region.